Phytotherapeutic agents on anxiety control in dentistry: a literature review (Research, Society and Development, 2021)
The aim of this work is to review the literature on the use of herbal medicines to control dental anxiety. For this purpose, articles were searched in the databases ScienceDirect, Pubmed and The Cochrane Library. 57 articles were included in this study. The research evidence points to Valeriana officinalis and Passiflora incarnata as the most studied herbal medicines for the control of anxiety, and their adverse effects are also investigated. Studies prove the relative safety of these medications, as well as their effectiveness, low cost, lower concentration of active ingredients with better effects and fewer side effects when compared to benzodiazepines. The use of these medicinal plants requires further clarification as to their real effectiveness, correct dosage and side effects in conscious sedation in Dentistry.